Defective graphene composite negative electrode microstructure and preparation method thereof

CN123017969APending Publication Date: 2026-10-30SHANG HAI SAI SAN BAO NENG YUAN JI SHU YOU XIAN GONG SI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610976031.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,目前尚无一套针对缺陷石墨烯复合负极的系统架构设计,即如何通过刻意调控石墨烯的缺陷类型和含量,在负极材料中同时构建电容型快速响应和电池型高容量双重储能通路的微观结构,从而兼顾高倍率充放电性能和长循环寿命

Benefits of technology

1、本发明高倍率性能显著提升,缺陷石墨烯构建的三维导电网络和离子传输通道极大降低了电极内阻,使电子和锂离子得以高速迁移。即使在10C甚至20C的大电流充放电下,本发明的复合负极仍能保持高比容量输出。例如,在石墨/缺陷石墨烯复合负极中,10C倍率下容量保持率达到90%以上,而传统纯石墨负极在同等条件下容量骤降至约50%。本发明的硅、锡基复合负极同样表现出远优于未复合石墨烯时的倍率特性。这意味着在电动汽车快充等场景下,电池可在几分钟内充入高状态的电量(SOC)而不过热或严重容量衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017969A_ABST
    Figure CN123017969A_ABST
Patent Text Reader

Abstract

The application discloses a kind of defective graphene composite negative microstructure and preparation method thereof: including electrochemical active material particles, defective graphene nanosheet;The defective graphene nanosheet has structural defect introduced by defect engineering;The electrochemical active material particles are compounded with defective graphene nanosheet, and form the composite structure that simultaneously includes capacitive type fast response path and battery type high capacity path on microscale scale.The defective graphene composite negative pole and preparation method thereof provided by the application have made breakthrough in material configuration and performance realization, and can provide key technical support for new generation high-power, high energy density lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery electrode material technology, and in particular relates to a defective graphene composite negative electrode microstructure and its preparation method. Background Technology

[0002] Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and other fields, but their overall performance is still limited by the anode material. Graphite anodes are currently the standard commercial anode material, but their theoretical capacity is only 372 mAh / g, which is insufficient to meet the demand for higher energy density batteries. Furthermore, under high-current charge-discharge conditions, graphite anodes are prone to restricted lithium-ion intercalation kinetics and surface lithium deposition, leading to decreased rate performance and safety issues. To improve battery capacity and power performance, researchers have developed a variety of novel high-capacity anode materials.

[0003] Silicon-based anode materials possess extremely high theoretical specific capacity (approximately 4200 mAh / g), but their volume expansion during charge and discharge exceeds 300%, leading to material pulverization, interfacial instability, and severely limited cycle life. Tin-based materials (such as metallic Sn or its oxide SnO2) also have theoretical capacities far exceeding those of graphite (Sn approximately 993 mAh / g), but they also exhibit significant volume effects, causing electrode structure pulverization and rapid capacity decay during cycling. Therefore, mitigating volume changes while maintaining high capacity, and improving conductivity and interfacial stability, are key challenges for next-generation anode materials.

[0004] To address the aforementioned issues, graphene, due to its ultra-high electrical conductivity, large specific surface area, and good mechanical flexibility, is widely used to improve the performance of anode materials. Graphene composite conductive networks can provide multiple electron transport channels for the anode, reducing internal resistance and ohmic polarization, and buffering volume changes in highly expandable materials such as silicon. For example, patent CN101849302A reports an anode that combines graphene nanosheets (NGP) with various active materials. Results show that adding graphene significantly improves the reversible capacity of the electrode, reduces first-cycle irreversible losses and internal resistance, and imparts faster charge-discharge characteristics to the battery. The flexible network of graphene can also prevent the agglomeration of active particles and reduce stress during cycling; the strain buffering effect extends cycle life. When the amount of graphene added reaches a certain threshold, a continuous three-dimensional conductive framework can be formed, improving the overall conductivity and thermal conductivity of the electrode. Another patent, CN103811718A, proposes preparing a graphite / graphene composite anode by uniformly dispersing nano-graphene sheets within a graphite matrix, ensuring close contact between the two phases and thus imparting high conductivity and excellent rate performance to the material. This composite material exhibits a conductivity of 2 g / cm³. 3 The electrical conductivity reaches 10 at compacted density. 3The graphene anode exhibits performance on the order of S / cm, a reversible capacity ≥360 mAh / g, an initial coulombic efficiency ≥90%, a capacity retention of over 95% at 10C rate, and retains over 90% of its capacity after 500 cycles. This demonstrates that optimizing the interfacial structure and dispersion of graphene and graphite particles can significantly improve the rate performance and long-cycle stability of traditional graphite anodes.

[0005] In the area of ​​silicon anodes, there are also technologies that attempt to use graphene to construct a three-dimensional support network to alleviate the volume effect of silicon.

[0006] In the field of tin-based anodes, several patents have explored graphene composites to improve performance. For example, CN103078095A discloses a method for preparing SnO2 / graphene composite anode materials, but the capacity of the resulting materials is relatively low. CN104600275A proposes the preparation of graphene-based hollow SnO2 anode materials, which requires long-term reaction in a high-pressure reactor and the use of strong reducing agents, making the process complex and difficult to scale up. Patents such as CN104953101A and CN102255072A respectively use graphene aerogel to support SnO2 and a two-step reflux calcination method to prepare SnO2 / graphene composite materials, but these methods suffer from problems such as long process flow, multiple precursor pre-preparation steps, or large particle size. Overall, these existing technologies have improved the capacity and rate performance of tin-based anodes to some extent, but most schemes still mainly treat graphene as a conductive additive or structural scaffold, failing to fully utilize the surface / edge defects of graphene to store charge or promote rapid ion migration. In other words, existing patents lack systematic research on the role of graphene defect engineering in electrodes.

[0007] In summary, existing technologies have recognized that combining graphene with anode materials can improve conductivity, buffer volume changes, and partially enhance rate performance. Some studies have also made preliminary attempts to introduce defects such as pores into graphene to optimize specific systems (e.g., ion diffusion in silicon / graphene films). However, there is currently no systematic architecture design for defective graphene composite anodes, i.e., how to deliberately control the type and content of graphene defects to simultaneously construct a microstructure with both capacitive fast response and battery-type high capacity energy storage pathways in the anode material, thereby achieving both high-rate charge / discharge performance and long cycle life. Furthermore, most existing solutions focus on a single material system, lacking a universal design and failing to cover a unified structural strategy for different types of anode materials such as graphite, silicon, and tin. Facing the urgent needs of electric vehicles, heavy-duty equipment, and fast-charging energy storage for high power density, high energy density, and long battery life, an innovative composite anode structure is urgently needed to overcome existing bottlenecks. This invention addresses the aforementioned technological gap by proposing a composite anode microstructure based on defective graphene and its preparation method, thereby achieving excellent performance and stable long lifespan of the anode material at high rates. Summary of the Invention

[0008] In view of this, the present invention aims to propose a defective graphene composite negative electrode microstructure and its preparation method to solve at least one technical problem in the background art.

[0009] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A defective graphene composite anode microstructure includes electrochemically active material particles and defective graphene nanosheets. The defective graphene nanosheets have structural defects introduced through defect engineering. The electrochemically active material particles are combined with defective graphene nanosheets to form a composite structure that simultaneously contains capacitive fast response pathways and battery-type high capacity pathways at the microscale.

[0010] Furthermore, the capacitive fast response pathway is composed of defect sites in the defective graphene nanosheets, and the defect sites are active sites for the rapid adsorption and desorption of lithium ions. The battery-type high-capacity pathway is composed of the electrochemically active material particles, which serve as carriers for reversible lithium-ion insertion / extraction or alloying reactions. The defective graphene nanosheets are interconnected to form a continuous electron conduction network, and the pores between the defective graphene nanosheets and their own pore defects constitute a three-dimensional lithium-ion diffusion channel.

[0011] The composite anode material comprises defective graphene composite anode material, including electrochemically active material particles and defective graphene nanosheets. The active material can be graphite, silicon, tin and their oxides, alloys, or other anode active materials capable of reversibly intercalating or alloying lithium ions, existing in the form of micron- or nano-sized particles. The graphene nanosheets undergo intentional defect introduction treatment, possessing structural defects of predetermined density and type, such as edge defects, surface nanopores, and heteroatom doping. The active particles and defective graphene construct a composite microstructure through tight coupling. For example, the surface of the active particles is coated with defective graphene sheets, forming a core-shell structure; Alternatively, active particles can be embedded in a conductive network constructed from defective graphene, forming a continuous, interpenetrating three-dimensional network structure. Preferably, the mass content of defective graphene in the composite material is 5% to 30%, which can be adjusted according to the type of active material and the application scenario to achieve a percolation threshold above the conductive network without excessively sacrificing the overall specific capacity. Through the above composition design, the composite material forms a unique structure at the microscopic level that combines a capacitive fast-response pathway with a battery-type high-capacity pathway.

[0012] Capacitor-Battery Hybrid Response Pathway: The defective graphene composite structure simultaneously incorporates two energy storage mechanism pathways at the microscale, achieving synergistic energy storage of "capacitor + battery". The capacitive pathway is provided by a graphene network with a high specific surface area and abundant defect sites. Nanopores and edge defects on the defective graphene serve as charge sites for the rapid adsorption / desorption of lithium ions, generating a rapid response similar to an electrochemical double-layer capacitor or pseudocapacitor during charge and discharge. Specifically, by tuning the degree of defect in the graphene to ensure the Raman D-peak to G-peak intensity ratio is within a predetermined range, a suitable defect concentration is indicated, thus maintaining high conductivity while providing additional charge storage sites. These active sites can rapidly adsorb lithium ions from the electrolyte at high rates, achieving instantaneous surface capacitance contributions and providing current response on millisecond to second timescales.

[0013] The battery-type pathway is provided by active material particles, which store charge through Faraday reactions such as lithium ion insertion / extraction within the particles or alloying with the particles, thus imparting high energy density to the electrode. The active particles are in close contact with graphene, effectively shortening the lithium ion diffusion path and reducing interfacial resistance. For example, when the active particles are graphite, lithium ions can rapidly enter the interlayer of graphite through the nanopores on the graphene sheet to complete insertion; when the active particles are silicon or tin-based, the flexible coating of graphene can buffer its volume changes, while graphene defect sites provide more nucleation sites, promoting reversible lithium alloying reactions.

[0014] The two pathways described above coexist and synergize within the same composite structure. The capacitive pathway provides a high-speed but moderate-capacity instantaneous response, while the battery-type pathway provides a slower but high-capacity continuous energy storage. This dual-mechanism synergy allows the electrodes to maintain high-capacity output even at high rates.

[0015] Interface coupling and transport networks: A stable interface is formed between defective graphene and active particles through physical coating, chemical bonding, or surface functional group interactions. On one hand, the highly conductive framework formed by graphene sheets connects the dispersed active particles, forming a continuous electron conduction network, enabling rapid electron transfer throughout the electrode. On the other hand, the pores / gaps formed between graphene sheets provide high-speed channels for electrolyte wetting and lithium-ion transport. In particular, the interconnected pores on the graphene sheets form a three-dimensional ion migration channel throughout the entire electrode, allowing lithium ions to shuttle three-dimensionally between particles. The synergistic effect of the electron and ion dual-phase network constructs a low-impedance, high-speed charge migration / transfer channel, enabling the composite negative electrode of this invention to efficiently transport charge even under high-current charging and discharging, significantly reducing concentration polarization and potential hysteresis.

[0016] Furthermore, the electrochemically active material is one or more carbon-based materials selected from graphite, artificial graphite, and petroleum coke; the defective graphene nanosheets are coated on the surface of the carbon-based material particles to form a core-shell structure, or form a layered mixed structure with the carbon-based material particles.

[0017] Furthermore, the electrochemically active material is nano-silicon or a silicon-based alloy; the defective graphene nanosheets coat and support the nano-silicon or silicon-based alloy particles to form a three-dimensional network framework structure, which is used to buffer volume changes during the charging and discharging process.

[0018] Furthermore, the electrochemically active material is tin or a tin compound, including SnO2, SnO, tin alloys, tin phosphides, or tin sulfides; nanoscale tin or tin compound particles are anchored on the surface of the defective graphene nanosheets, and the anchoring is achieved through graphene defect sites.

[0019] Furthermore, the structural defects of the defective graphene nanosheets are selected from one or more combinations of edge unsaturated bond defects, surface nanopore defects, and heteroatom doping point defects; Defect types and control methods: In this invention, defective graphene refers to structural defects introduced into the graphene structure through specific means, including but not limited to the following: Edge and lattice defects, such as unsaturated bonds, broken six-membered rings, and Stone-Wales defects at the edges of graphene sheets. These defects can be generated on graphene sheets by methods such as high-energy ball milling and plasma bombardment, increasing the number of active boundary sites and thus improving lithium-ion adsorption capacity and pseudocapacitive effect.

[0020] Surface nanopores, forming through-holes or pores with diameters of 1–100 nm on the graphene plane, can be achieved through methods such as directional etching with oxidants, chemical etching, or high-temperature thermal ablation. The introduction of nanopores increases the specific surface area of ​​graphene and acts as a fast channel for lithium ions, enabling lithium ions to penetrate the graphene sheets rather than just migrating along the surface, thus significantly improving the ion diffusion rate.

[0021] Heteroatom doping introduces point defects into the graphene lattice, forming substitutional or embedded defect sites. Doping can modulate the electronic structure of graphene, enhancing lithium-ion adsorption and bonding, while simultaneously creating additional defect-state lithium storage sites. Typical methods include chemical vapor deposition doping, nitrogen atmosphere heat treatment (such as ammonia annealing to introduce N), and plasma deposition to control the type and concentration of heteroatoms.

[0022] Through the above defect engineering methods, the defect types and densities of graphene can be designed as needed. The preferred defective graphene of this invention has the following characteristics: specific surface area ≥ 300 m².2 / g, with a Raman spectrum D-peak to G-peak intensity ratio between 0.5 and 1.5 (corresponding to moderate defects), and an oxygen-containing functional group content of 5–15 at% or a heteroatom doping content of 1–10 at% (determined according to the specific defect introduction method). The graphene obtained through this regulation possesses both good conductivity and abundant active defect sites, which can effectively support the realization of a dual-pathway synergistic energy storage mechanism in the composite anode.

[0023] The Raman spectrum of the defective graphene nanosheets has an intensity ratio of D peak to G peak of 0.5–1.5, and a specific surface area of ​​not less than 300 m². 2 / g; The defective graphene nanosheets in the defective graphene composite anode material have a mass content of 1% to 50%, preferably 5% to 30%. Preferably, the heteroatoms in the heteroatom doping point defects are nitrogen atoms, boron atoms, phosphorus atoms, or oxygen atoms, and the heteroatoms replace carbon atoms in the graphene lattice or are embedded in the graphene lattice.

[0024] The method for preparing the above-mentioned defective graphene composite anode microstructure is characterized by comprising the following steps: S1: Defective treatment is performed on the original graphene material to obtain defective graphene nanosheets with predetermined defect density and defect type; S2: The defective graphene nanosheets obtained in step S1 are mixed and composited with electrochemically active material particles to form a uniform graphene-active material composite. S3: The composite obtained in step S2 is mixed with a binder, coated onto a current collector, dried and compacted to obtain a defective graphene composite negative electrode.

[0025] Furthermore, the defect treatment in step S1 is selected from one or more combinations of oxidant chemical etching, plasma bombardment, high-energy ball milling, and heteroatom doping heat treatment; Preferably, in step S1, a chemical etching method is used to form surface nanopore defects on the graphene sheet, and the diameter of the surface nanopores is 1 to 100 nm; the chemical etching method includes reacting a suspension of graphene oxide with a strong oxidant, followed by a reduction treatment.

[0026] Preferably, in step S1, edge defects and / or lattice defects are generated in the graphene by plasma treatment or high-energy ball milling; The plasma treatment power is 50-200W, and the treatment time is 1-10 minutes; The high-energy ball mill operates at a speed of 100–500 rpm and a milling time of 2–10 hours. Preferably, in step S1, a heteroatom doping method is used to introduce doping point defects into the graphene lattice; the heteroatom doping method includes heat-treating the graphene in a nitrogen-containing or boron-containing atmosphere at a temperature of 500-1000°C for 0.5-5 hours. Further, in step S2, the composite method is selected from one of solution blending deposition, self-assembly coating, vapor deposition, in-situ growth synthesis, or mechanical mixing; In step S2, defective graphene nanosheets are dispersed in a solvent to form a dispersion, electrochemically active material particles are added, and the defective graphene nanosheets are uniformly loaded onto the surface of the electrochemically active material particles by ultrasonication or stirring. Then, the solvent is removed by freeze drying, spray drying or vacuum filtration to obtain a composite precursor. Subsequently, heat treatment is performed at a temperature not exceeding 500°C to enhance the interfacial bonding and conductivity between the defective graphene nanosheets and the electrochemically active material particles. Preferably, when the electrochemically active material is a silicon or tin compound precursor, the defective graphene nanosheet dispersion is mixed with the silicon or tin-containing precursor, so that the precursor is adsorbed onto the defective graphene nanosheets, and then a composite of nano-silicon or nano-tin-based compound and defective graphene nanosheets is generated in situ through one-step pyrolysis or one-step reduction treatment.

[0027] Specifically, the method for preparing the defective graphene composite anode material provided by the present invention includes the following main steps: Graphene defect introduction: The original graphene material is subjected to defect treatment to obtain defective graphene with a set defect density. The treatment method can be one or a combination of oxidant etching, plasma bombardment, high-energy ball milling, heteroatom doping heat treatment, etc., to introduce the aforementioned edge defects, surface pores, or point defects into the graphene sheets. The type and concentration of graphene defects are adjusted by controlling parameters such as treatment time, temperature, and dosage.

[0028] Composite assembly: Defect-treated graphene is mixed with selected anode active material particles in a certain proportion to form a uniform graphene-active material composite. Composite methods can include solution blending deposition, self-assembly coating, vapor deposition, growth synthesis, or mechanical mixing. For example, for graphite anodes, a defective graphene aqueous dispersion can be mixed with graphite powder and then vacuum filtered to form a film, or spray-dried to obtain a composite powder. For nano-silicon, nano-tin, and other particles, a solution method can be used to deposit graphene in situ onto the particle surface, or a graphene-particle aerogel can be obtained through vacuum filtration and low-temperature heat treatment to fix the structure.

[0029] Electrode preparation: The obtained composite is mixed with an appropriate amount of binder and coated onto the current collector to prepare an electrode sheet. Since the composite material itself possesses high conductivity and structural stability, additional conductive carbon additives can be reduced or even eliminated. The electrode sheet is dried and rolled to achieve the required compaction density before being assembled into a battery for testing. Preferably, the compaction density and graphene content are optimized experimentally to ensure the continuity of the conductive network while also considering the energy density of the electrode.

[0030] The application of the above-mentioned defective graphene composite anode microstructure in lithium-ion batteries is characterized in that the defective graphene composite anode microstructure is used to prepare the anode of electric vehicle power batteries, heavy equipment batteries or high-power energy storage batteries; the battery containing the anode has a discharge capacity retention rate at a rate of 5C or higher that is at least 20% higher than that of the control anode without defective graphene, and the cycle life is extended by more than 50%.

[0031] Furthermore, the defective graphene composite anode material is used to improve the high-rate charge-discharge performance and cycle life of sodium-ion batteries or potassium-ion batteries.

[0032] Compared with existing technologies, the defective graphene composite anode microstructure and its preparation method described in this invention have the following advantages: 1. This invention significantly improves high-rate performance. The three-dimensional conductive network and ion transport channels constructed from defective graphene greatly reduce the internal resistance of the electrode, enabling high-speed migration of electrons and lithium ions. Even under high-current charge-discharge of 10C or even 20C, the composite anode of this invention can still maintain high specific capacity output. For example, in the graphite / defective graphene composite anode, the capacity retention rate at 10C reaches over 90%, while the capacity of the traditional pure graphite anode drops sharply to about 50% under the same conditions. The silicon- and tin-based composite anode of this invention also exhibits rate performance far superior to that without graphene composite. This means that in scenarios such as fast charging of electric vehicles, the battery can be charged to a high state of charge (SOC) within minutes without overheating or severe capacity decay.

[0033] 2. The present invention extends the cycle life. The flexible framework formed by graphene effectively suppresses the mechanical stress concentration caused by the volume deformation of active particles during repeated lithium insertion and extraction, and buffers the side reactions at the electrolyte-electrode interface through its defect sites, reducing the repeated rupture and regeneration of the SEI film during cycling. Tests show that the composite anode of the present invention retains more than 85% of its initial capacity after 500 cycles of high-rate charge-discharge, while the capacity retention rate of the control electrode without graphene is less than 60%. For silicon and tin materials with severe volume expansion, the coating and supporting effect of defective graphene significantly improves the cycle life, increasing the number of stable cycles from tens to hundreds. This indicates that in the composite structure of the present invention, graphene produces a synergistic effect at the interface between the active particles and the electrolyte: internally buffering particle deformation and externally stabilizing the electrolyte interface, achieving a dual-interface synergistic improvement in cycle stability.

[0034] 3. The capacity improvement and first-cycle efficiency enhancement of this invention are due to the fact that defective graphene itself provides a certain amount of additional reversible capacity (through the surface pseudocapacitive effect and defect-adsorbed lithium mechanism), resulting in a higher total capacity of the composite electrode compared to when no graphene is added. For example, in graphite-based composite anodes, because the graphene defect sites contribute a portion of the charge storage, the reversible specific capacity exceeds the theoretical value of 372 mAh / g for traditional graphite, reaching approximately 400–420 mAh / g. For high-capacity silicon-tin material systems, the introduction of graphene helps improve the first-cycle coulombic efficiency: its stable surface defects facilitate the in-situ formation of a stable SEI film, reducing irreversible losses and generally improving the first-cycle efficiency by 5–10 percentage points.

[0035] 4. The versatility and scalability of the process of this invention: The defective graphene composite structure proposed in this invention has strong versatility and can be applied to different types of anode materials. Appropriate defect introduction methods and composite processes can be selected according to the characteristics of the active material to prepare various composite anode materials such as graphite / graphene, silicon / graphene, and tin-based / graphene. The methods used in each step of this invention (chemical etching, high-energy ball milling, solution deposition, etc.) are all mature and feasible industrial technologies, with mild conditions, short cycles, low costs, and easy scale-up. For example, in a preferred process of this invention, the SnO2 / graphene composite material can be obtained by in-situ loading of a tin precursor on graphene oxide using a solution method and then calcining it in one step, avoiding cumbersome multi-step reactions and long-term high-temperature and high-pressure treatment. Therefore, the solution of this invention has good process operability and industrialization prospects.

[0036] 5. The key feature of this invention lies in the introduction of defect engineering concepts into the design of the negative electrode microstructure. It innovatively integrates the rapid response mechanism of supercapacitors into the battery negative electrode, forming a dual-pathway synergistic energy storage mechanism. This structural design differs from traditional methods that simply add conductive agents or simply combine two materials; instead, it constructs a new energy storage mechanism coupling within the material itself. A search of published literature and patents reveals no precedent for using graphene defects to construct a negative electrode architecture with a capacitor-battery hybrid energy storage pathway. Therefore, this invention possesses significant novelty and inventiveness. The composite structure of this invention significantly improves the high-rate charge-discharge performance and long cycle life of batteries, directly responding to the practical needs of electric vehicle fast charging, grid frequency regulation energy storage, and other fields, and has extremely high industrial application value.

[0037] 6. The defective graphene composite anode and its preparation method provided by this invention have achieved breakthroughs in both material configuration and performance realization, and are expected to provide key technical support for the next generation of high-power, high-energy-density lithium-ion batteries. Attached Figure Description

[0038] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic diagram of a typical microstructure of a defective graphene composite anode material (a is a structural model of defective graphene-coated active material particles, b is a schematic diagram of the lithium-ion transport mechanism of the defective graphene material. The figure shows the morphological characteristics of the composite material: sheet-like graphene surrounds and covers the surface of spherical / granular active material, forming a clear core-shell interface; at the same time, the graphene sheets interweave to form a three-dimensional conductive network and channels. The inset shows a magnified interface area, illustrating the porous structure on the graphene sheet and its tight bonding with the surface of the active particles). Figure 2 This diagram illustrates the charge migration pathways in a defective graphene composite anode (showing the transport paths of electrons and lithium ions within the composite electrode: electrons are rapidly conducted through the conductive network formed by the graphene sheets (solid arrows), while lithium ions diffuse and shuttle between the particles and graphene at the interface through the pores and defect channels between the graphene sheets (dashed arrows). The diagram also illustrates the simultaneous existence of two energy storage mechanisms: capacitive surface adsorption (occurring at graphene defect sites) and battery-type particle embedding, and their synergistic effect). Figure 3 This is a Raman displacement intensity diagram of the defective graphene described in Embodiment 1 of the present invention; Figure 4 This diagram shows the capacity retention of the defective graphene composite anode material (dashed line) and the traditional pure anode material (solid line) at different charge-discharge rates. Figure 5 XPS test images of the defective graphene composite anode described in Example 2 of this invention (a is the full spectrum, b is the N 1s high-resolution spectrum, and c is the O 1s high-resolution spectrum). Figure 6 This is the XPS test image of the defective graphene composite negative electrode shown in Example 3 of the present invention; Figure 7 The images shown are SEM / TEM images of the defective graphene composite anode shown in Example 3 of this invention (a is an SEM image, b is a TEM image). Figure 8 The electrochemical impedance spectroscopy of the defective graphene composite negative electrode shown in Example 3 of this invention is shown. Figure 9 The images shown are atomic force microscopy images of the defective graphene composite negative electrode shown in Example 3 of the present invention (a is the adhesion force diagram of pure SnO2 particles, and b is the adhesion force diagram of graphene-coated SnO2 particles). Detailed Implementation

[0039] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other.

[0040] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0041] Example 1: Graphite / Defective Graphene Composite Anode Material Artificial graphite was selected as the negative electrode active material, with a particle size D. 50 They are approximately 15 μm in size and spherical in shape. The graphene raw material used is commercially available graphene oxide (GO) powder, with a specific surface area of ​​approximately 400 m². 2 / g. First, GO was pre-reduced to improve its conductivity. The specific process was as follows: 5g of graphene oxide (GO) powder was weighed and added to 1000mL of deionized water, and dispersed under ultrasonic conditions for 1h to obtain a uniform GO suspension with a concentration of approximately 5mg / mL. Then, ascorbic acid (vitamin C) was added as a green reducing agent, with an addition amount five times the mass of GO. The mixture was heated to 95℃ under magnetic stirring and reacted for 3h. During the reaction, epoxy groups, hydroxyl groups, and some carboxyl groups in the GO sheets were gradually removed, increasing the degree of graphitization and significantly enhancing conductivity. After the reaction, the mixture was naturally cooled to room temperature, and the solid product was collected by filtration and repeatedly washed with deionized water until the pH of the filtrate reached 6-7. Subsequently, it was vacuum dried at 60℃ for 12h to obtain pre-reduced graphene oxide (rGO) powder. Transmission electron microscopy characterization showed that its sheet thickness was approximately 3-5 layers, still retaining a small amount of oxygen-containing functional groups (oxygen content approximately 8-12 at%), which is beneficial for subsequent defect etching and stable dispersion. Then, rGO was subjected to gentle oxidative etching to introduce nanoporous defects. Specifically, rGO was dispersed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide, the temperature was controlled at 60°C, and the reaction was carried out for 2 hours. Afterwards, it was thoroughly washed with water, neutralized, and dried to obtain defective graphene with nanopores on its surface. The Raman spectroscopy of this defective graphene was measured. Figure 3 As shown, I D / I G ≈1.1, BET specific surface area increased to approximately 550m² 2 / g, with an average pore size of approximately 20nm.

[0042] For composite assembly, the aforementioned defective graphene was dispersed in deionized water, and after adding a small amount of surfactant, it was ultrasonically dispersed for 30 min to obtain a stable suspension (concentration of approximately 2 mg / mL). The surfactant is preferably one or both of the anionic surfactants sodium dodecyl sulfate (SDS) and sodium dodecylbenzene sulfonate (SDBS); more preferably, SDBS is used, with an addition amount of 2–10 wt% of the defective graphene mass, preferably 5 wt%. SDBS can adsorb onto the graphene surface through π-π interactions, effectively inhibiting the recombination of graphene sheets and improving the dispersion stability of defective graphene in the aqueous phase, resulting in no significant sedimentation of the obtained suspension after standing for 24 h. Then, graphite powder was added to the suspension, and the temperature was slowly raised to approximately 80°C under stirring to gradually evaporate the water. As the solvent evaporated, the graphite particles were gradually coated by the graphene sheets, forming a uniformly deposited graphite / graphene composite. The resulting wetted deposit was dried under vacuum conditions and gently ground to obtain the graphite / defective graphene composite powder. The composite powder was weighed and found to contain approximately 10 wt% graphene.

[0043] Electrode preparation and testing: The above-mentioned composite powder was mixed with a small amount of PVDF binder at a mass ratio of 90:10, and N-methylpyrrolidone (NMP) solvent was added to prepare a slurry. This slurry was then uniformly coated onto a copper foil current collector to prepare an electrode sheet. The electrode was vacuum dried at 120℃ for 12 hours, and the compaction density was adjusted to approximately 1.5 g / cm³. 3 The electrode sheets were then assembled with lithium metal sheets to form a CR2032 coin cell. The electrolyte used was a conventional carbonate electrolyte consisting of 1 M LiPF6 dissolved in a 1:1 volume ratio of EC / DMC mixed solvent. Electrochemical performance tests, including charge-discharge at different rates and cycle life tests, were conducted at room temperature.

[0044] Figure 4 The rate performance curves of the graphite / defect graphene composite anode and the control sample (pure graphite anode) are shown: at 0.2C, the specific capacity of the composite anode is approximately 380 mAh / g, close to the theoretical value of graphite; when the rate is increased to 1C, the capacity remains at approximately 370 mAh / g, with only slight decay; even at a high rate of 5C, it can still output approximately 330 mAh / g, with a capacity retention of over 90%. In contrast, under the same conditions, the pure graphite electrode without graphene has a capacity of less than 250 mAh / g at 5C, showing a significant decrease. Furthermore, cycle life testing shows that after 500 cycles of 2C charge-discharge cycles, the capacity retention of the composite anode is approximately 88%, significantly higher than the 67% of the pure graphite anode. These results demonstrate that the introduction of defect graphene effectively endows the graphite anode with superior high-rate performance and long-cycle stability.

[0045] In this embodiment, the nanopores on the graphene sheet provide a fast channel for lithium ions to move between graphite particles, alleviating the bottleneck of solid-state diffusion limitation in traditional graphite anodes at high rates. Simultaneously, the conductive network constructed by graphene reduces the contact resistance between particles, allowing electrons to conduct rapidly throughout the entire electrode. Electrochemical tests show that the composite electrode maintains close to its theoretical capacity at high rates, indicating that a significant portion of the charge is contributed by capacitive adsorption on the graphene surface, resulting in instantaneous discharge. This capacitive response effectively compensates for the limitation of lithium-ion intercalation in graphite within a short time, achieving a balance between capacity and rate: maintaining a high capacity close to the theoretical value of graphite while achieving a rapid output capability similar to a supercapacitor.

[0046] Example 2: Silicon / Defect Graphene Composite Anode Material For raw material selection, nano-silicon powder with a particle size of approximately 100 nm and a silicon purity >99% was chosen as the negative electrode active material (theoretical specific capacity approximately 4200 mAh / g). Graphene raw material was selected as an aqueous dispersion of graphene oxide (GO) (concentration 5 mg / mL). To introduce defects into the graphene and enhance its structure, a combined chemical etching and reduction method was employed: a mixed solution of ammonium persulfate and nitric acid was added to the GO dispersion, and the reaction was carried out at 80°C for 1 hour to etch nanopores into the graphene sheets. Ammonium persulfate preferentially oxidizes the carbon framework to form pore defects. Subsequently, ascorbic acid (vitamin C) was added as a reducing agent, and the reaction was continued at 95°C for 2 hours to partially reduce GO to rGO and introduce a small amount of nitrogen doping derived from the decomposition products of vitamin C. The reaction product was filtered, washed, and vacuum dried to obtain powdered defect graphene. Figure 5 As shown, XPS testing revealed that the defective graphene contained approximately 4 at% N and 10 at% O; Raman spectroscopy... D / I G ≈0.9, specific surface area approximately 600 m² 2 / g, which has abundant pores and heteroatom point defects.

[0047] Composite Assembly: The defective graphene powder was redispersed in deionized water to prepare a suspension with a concentration of approximately 3 mg / mL. A certain amount of silicon nanoparticles was added, and the mixture was ultrasonically stirred at room temperature for 30 minutes to allow the graphene sheets to fully adsorb and encapsulate the silicon particles. The suspension was then rapidly frozen, and the solvent was removed by freeze-drying to obtain a fluffy silicon / graphene aerogel composite. This composite was then heat-treated at 400°C for 2 hours in an inert atmosphere to remove residual oxygen functional groups and improve the conductivity of graphene, while simultaneously promoting a strong contact between the silicon particles and the graphene. The final silicon / defective graphene composite material exhibited a black porous network structure, with a silicon content of approximately 50 wt%.

[0048] Electrode preparation and testing: Silicon / defect graphene composite powder was mixed with SuperP conductive carbon and LA133 aqueous binder at a mass ratio of 80:10:10. Deionized water was added and stirred to form a homogeneous slurry, which was then coated onto a copper foil current collector. The electrode was vacuum dried at 80℃ for 12 hours before use. CR2032 coin cell half-cells were assembled, using lithium metal as the counter electrode and 1M LiPF6 (EC / DEC = 1:1, volume ratio) carbonate electrolyte. The capacity, voltage, and cycle performance of the cell were tested in constant current mode.

[0049] The performance results are shown in Table 1. The silicon / defect graphene composite anode exhibits a specific capacity of approximately 1500 mAh / g (calculated based on the total mass of the composite material) at the first 0.1C discharge, with an initial coulombic efficiency of approximately 88%. In contrast, the pure nano-silicon electrode typically has an initial efficiency below 70% due to severe initial irreversible degradation. Rate testing shows that at a 1C current density, the composite anode has a capacity of approximately 1200 mAh / g; even at a high current of 5C, it can still output approximately 800 mAh / g, with a specific capacity retention of over 65%. The pure silicon electrode, however, experiences capacity degradation of more than half at 1C and is almost unable to discharge effectively at 5C. Regarding cycle stability, the composite anode retains approximately 82% capacity after 200 cycles at a 0.5C current density, while the pure silicon electrode almost loses its capacity due to pulverization failure after only ten charge-discharge cycles. Therefore, the defect graphene network significantly improves the practical performance of the silicon anode.

[0050] Table 1

[0051] The superior performance of the silicon / graphene composite anode stems from a synergistic effect of multiple factors. First, defective graphene constructs a three-dimensional conductive framework and ion channels, accelerating lithium-ion diffusion within the electrode and maintaining overall conductivity, ensuring a sufficient supply of lithium ions and electrons around the silicon particles even at high currents. Second, the flexible coating of graphene on the silicon particles effectively buffers the stress generated by the large volume changes in silicon, preventing cracking and detachment of active particles. In particular, the pores and defects on the graphene surface provide buffer space and nucleation sites for lithium deposition, guiding the formation of a stable LixSi phase and a stable SEI film during cycling. Third, the pseudocapacitive effect at the graphene defects contributes to the initial capacity during cycling, reducing the depth of lithium intercalation in silicon, thereby reducing irreversible losses and improving first-cycle efficiency. In summary, the introduction of defective graphene synergistically improves the performance of the silicon anode from multiple aspects, including conductivity, structural integrity, and interfacial chemistry, achieving a balance between high capacity and long lifetime.

[0052] Example 3: Tin-based / defective graphene composite anode material For raw material selection, tin oxide (SnO2) was chosen as the representative tin-based anode material, and nano-SnO2 particles were generated through in-situ reaction of chemical precursors. The graphene raw material was graphene oxide (GO) powder. The tin precursor was an organotin salt, dibutyltin dilaurate.

[0053] For composite assembly preparation, GO was dispersed in anhydrous ethanol to prepare a suspension with a concentration of approximately 0.5 mg / mL. Dibutyltin dilaurate was added at room temperature to a concentration of approximately 0.02 mmol / mL. After magnetic stirring and homogenization, the mixture was heated to 50°C, and the ethanol solvent was slowly evaporated. As the solvent evaporated, a brown, viscous precursor was obtained, in which the organotin salt precursor was uniformly adsorbed on the surface of the graphene sheets. This precursor was calcined in air at 300°C for 1 hour and then naturally cooled to room temperature to obtain the tin-based / graphene composite material. During calcination, the organotin salt underwent a pyrolysis reaction, generating SnO2 nanoparticles with a diameter of 5–10 nm in situ on the graphene sheets; simultaneously, the organic ligands partially decomposed and carbonized, forming a conductive matrix together with the graphene. The resulting composite material contained approximately 15% graphene and approximately 85% SnO2 loading. Figure 6 As shown, XRD analysis revealed that SnO2 is a tetragonal phase crystal, and the graphene matrix exhibits amorphous carbon characteristics. Figure 7 As shown, SEM / TEM observations revealed that SnO2 nanoparticles were uniformly anchored on the surface of the graphene sheet, with the particles separated by the graphene sheet and no obvious agglomeration.

[0054] Electrode preparation and testing: SnO2 / defect graphene composite powder was mixed with SuperP conductive carbon and PVDF binder at a mass ratio of 80:10:10. NMP solvent was added and stirred to form a slurry, which was then uniformly coated onto an aluminum foil current collector. The electrode was vacuum dried at 80℃ for 12 hours, and then rolled to increase its density (approximately 1.6 g / cm³). 3 The electrodes were assembled with lithium metal counter electrodes to form CR2032 coin cells. Constant current charge-discharge tests were performed within a voltage window of 0.01–2.0V, and rate performance and cycle life were evaluated.

[0055] This SnO2 / defective graphene composite anode achieved a specific capacity of up to 1000 mAh / g at the first 0.1C discharge (exceeding the theoretical SnO2 capacity of 782 mAh / g based on the total mass of the composite material, indicating an additional contribution from surface capacity), with an initial coulombic efficiency of approximately 75%, a significant improvement compared to the graphene-free control group (<60%). After 10 low-rate activation cycles, the stable reversible capacity of the material reached approximately 800 mAh / g. Subsequently, increasing the current density to 1 A / g (approximately 2.7C rate), the composite anode maintained a capacity of approximately 500 mAh / g; even at a discharge rate of 2.5 A / g (approximately 7C), a capacity output of approximately 400 mAh / g was still achieved. These values ​​are significantly higher than those of the pure SnO2 electrode without graphene (the control showed a capacity of <300 mAh / g at 1 A / g and almost no capacity output at 2.5 A / g). Cyclic test results show that after 200 charge-discharge cycles at a current of 1 A / g, the composite electrode retains approximately 85% of its capacity, while the control electrode's capacity decays to less than 50% after approximately 100 cycles.

[0056] Tin-based anodes undergo conversion and alloying reactions during lithium-ion intercalation, and repeated cycles can easily lead to electrode structure pulverization and failure. In the SnO2 / graphene composite material prepared in this invention, graphene not only exists as a conductive network but also plays a role in in-situ generation and anchoring of nanoparticles through its defect sites. On the one hand, the graphene sheet restricts the growth size of SnO2 particles, maintaining them at the several nanometer scale, thereby increasing the interfacial contact area and shortening the Li-ion intercalation time. + The diffusion pathway promotes rapid reactions and improves the utilization rate of active materials. On the other hand, defects and functional groups on the graphene surface (partially from incompletely reduced oxygen groups) form strong interfacial bonds with SnO2 particles (such as the possible formation of C–O–Sn bonds), effectively preventing particle aggregation and shedding during cycling. During electrochemical processes, the defect sites of graphene may also participate in a certain degree of pseudocapacitive lithium storage, enabling it to still provide considerable capacity at high rates. When the rate increases, the graphene network carries the main current, responding instantly through rapid adsorption / desorption of surface charges, while the deep conversion reaction of SnO2 can proceed under more moderate conditions, thereby maintaining capacity at high current densities. This synergistic energy storage mechanism enables the SnO2 / defect graphene composite anode to possess both high capacity and high power characteristics. For example, based on the data from this embodiment, it is estimated that a battery using this composite anode can be charged to 50% capacity in approximately 5 minutes and exhibits no significant performance degradation after hundreds of cycles, demonstrating excellent application prospects.

[0057] like Figure 8 As shown, electrochemical impedance spectroscopy (EIS) tests revealed that the charge transfer impedance of the composite anode in the mid-to-high frequency region was significantly lower than that of the uncomposite control electrode (approximately 40% of the latter), indicating that the conductive network constructed by defective graphene significantly reduced interfacial resistance and improved electron / ion transport rates. X-ray photoelectron spectroscopy (XPS) analysis showed that after hundreds of cycles, the SEI film on the surface of the composite anode had a higher proportion of inorganic components (such as LiF) and was thinner and more uniform, while the SEI film of the control electrode was thicker and richer in organic components, indicating that the introduction of defective graphene helps to form a stable and dense interfacial film, slowing down repeated SEI rupture. Figure 9 As shown, atomic force microscopy (AFM) adhesion tests revealed that the surface adhesion of graphene-coated active particles was significantly higher than that of pure active particles, reflecting a tighter and stronger bond between graphene and the particle interface. These characterization results further demonstrate the superiority of the composite structure of this invention in reducing impedance and stabilizing the interface, which is consistent with the conclusions of electrochemical performance tests.

[0058] The above embodiments mainly focus on three typical anode active materials: graphite, silicon, and SnO2, and respectively present the design and effects of defective graphene composites. The technical solution of this invention is not limited to these materials and can be extended to other anode material systems and energy storage systems. The defective graphene composite strategy is also applicable to anodes of various materials such as tin-based alloys (e.g., SnSb alloys), transition metal oxides (e.g., Fe3O4, CoO), metal phosphides, or sulfides (e.g., FeP, MoS2) to improve their rate performance and cycle stability. Furthermore, the design concept of composite anodes in this invention is also applicable to emerging energy storage systems such as sodium-ion batteries and potassium-ion batteries—for example, in sodium-ion batteries, defective graphene can be composited with carbon-based anodes such as hard carbon to improve the rapid storage capacity and cycle life of sodium ions; in potassium-ion battery anodes, defective graphene networks are expected to alleviate the kinetic problems of large-size potassium ion intercalation. Furthermore, different defect introduction methods and graphene composite methods can be adjusted as needed: for example, large-area nitrogen-doped graphene films prepared by CVD can be used directly as negative electrode current collectors and active material carriers, or defective graphene can be combined with conductive polymers to form a composite coating to coat silicon particles, etc. These variations all fall within the scope of this invention, demonstrating the versatility and flexibility of the invention.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A defective graphene composite anode microstructure, characterized in that: Including electrochemically active material particles and defective graphene nanosheets; The defective graphene nanosheets have structural defects introduced through defect engineering. The electrochemically active material particles are combined with defective graphene nanosheets to form a composite structure that simultaneously contains capacitive fast response pathways and battery-type high capacity pathways at the microscale.

2. The defective graphene composite anode microstructure according to claim 1, characterized in that: The capacitive fast response pathway is formed by the defect sites of the defective graphene nanosheets, and the defect sites are active sites for the rapid adsorption and desorption of lithium ions. The battery-type high-capacity pathway is composed of the electrochemically active material particles, which serve as carriers for reversible lithium-ion insertion / extraction or alloying reactions. The defective graphene nanosheets are interconnected to form a continuous electron conduction network, and the pores between the defective graphene nanosheets and their own pore defects constitute a three-dimensional lithium-ion diffusion channel.

3. The defective graphene composite anode microstructure according to claim 1, characterized in that: The electrochemically active material is one or more carbon-based materials selected from graphite, artificial graphite, and petroleum coke; the defective graphene nanosheets are coated on the surface of the carbon-based material particles to form a core-shell structure, or form a layered mixed structure with the carbon-based material particles.

4. The defective graphene composite anode microstructure according to claim 1, characterized in that: The electrochemically active material is nano-silicon or silicon-based alloy; the defective graphene nanosheets coat and support the nano-silicon or silicon-based alloy particles to form a three-dimensional network framework structure, which is used to buffer volume changes during charging and discharging.

5. The defective graphene composite anode microstructure according to claim 1, characterized in that: The electrochemically active material is tin or a tin compound, and the tin compound includes SnO2, SnO, tin alloys, tin phosphides, or tin sulfides. The defective graphene nanosheets have nanoscale tin or tin compound particles anchored on their surface, the anchoring being achieved through graphene defect sites.

6. The defective graphene composite anode microstructure according to claim 1, characterized in that: The structural defects of the defective graphene nanosheets are selected from one or more combinations of edge unsaturated bond defects, surface nanopore defects, and heteroatom doping point defects. The Raman spectrum of the defective graphene nanosheets has an intensity ratio of D peak to G peak of 0.5–1.5, and a specific surface area of ​​not less than 300 m². 2 / g; The defective graphene nanosheets in the defective graphene composite anode material have a mass content of 1% to 50%, preferably 5% to 30%. Preferably, the heteroatoms in the heteroatom doping point defects are nitrogen atoms, boron atoms, phosphorus atoms, or oxygen atoms, and the heteroatoms replace carbon atoms in the graphene lattice or are embedded in the graphene lattice.

7. The method for preparing the defective graphene composite anode microstructure according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1: Defective treatment is performed on the original graphene material to obtain defective graphene nanosheets with predetermined defect density and defect type; S2: The defective graphene nanosheets obtained in step S1 are mixed and composited with electrochemically active material particles to form a uniform graphene-active material composite. S3: Mix the composite obtained in step S2 with the binder, coat it onto the current collector, and then dry and compact it to obtain a defective graphene composite negative electrode.

8. The preparation method according to claim 7, characterized in that, The defect treatment in step S1 is selected from one or more combinations of oxidant chemical etching, plasma bombardment, high-energy ball milling, and heteroatom doping heat treatment; Preferably, in step S1, a surface nanopore defect is formed on the graphene sheet using a chemical etching method, wherein the diameter of the surface nanopore is 1-100 nm; the chemical etching method includes reacting a suspension of graphene oxide with a strong oxidizing agent, followed by a reduction treatment; Preferably, in step S1, edge defects and / or lattice defects are generated in the graphene by plasma treatment or high-energy ball milling; The plasma treatment power is 50-200W, and the treatment time is 1-10 minutes; The high-energy ball mill operates at a speed of 100–500 rpm and a milling time of 2–10 hours. Preferably, in step S1, a heteroatom doping method is used to introduce doping point defects into the graphene lattice; the heteroatom doping method includes heat-treating the graphene in a nitrogen-containing or boron-containing atmosphere at a temperature of 500–1000°C for 0.5–5 hours.

9. The preparation method according to claim 7, characterized in that, In step S2, the composite method is selected from one of solution blending deposition, self-assembly coating, vapor deposition, in-situ growth synthesis or mechanical mixing; In step S2, defective graphene nanosheets are dispersed in a solvent to form a dispersion, electrochemically active material particles are added, and the defective graphene nanosheets are uniformly loaded onto the surface of the electrochemically active material particles by ultrasonication or stirring. Then, the solvent is removed by freeze drying, spray drying or vacuum filtration to obtain a composite precursor. Subsequently, heat treatment is performed at a temperature not exceeding 500°C to enhance the interfacial bonding and conductivity between the defective graphene nanosheets and the electrochemically active material particles. Preferably, when the electrochemically active material is a silicon or tin compound precursor, the defective graphene nanosheet dispersion is mixed with the silicon or tin-containing precursor, so that the precursor is adsorbed onto the defective graphene nanosheets, and then a composite of nano-silicon or nano-tin-based compound and defective graphene nanosheets is generated in situ through one-step pyrolysis or one-step reduction treatment.

10. The application of the defective graphene composite negative electrode microstructure according to any one of claims 1 to 6 in lithium-ion batteries, characterized in that, The defective graphene composite anode microstructure is used to prepare anodes for electric vehicle power batteries, heavy equipment batteries or high-power energy storage batteries; batteries containing this anode have a discharge capacity retention rate at a rate of 5C or higher that is at least 20% higher than that of the control anode without defective graphene, and a cycle life that is extended by more than 50%. Preferably, the defective graphene composite anode material is used to improve the high-rate charge-discharge performance and cycle life of sodium-ion batteries or potassium-ion batteries.

Citation Information

Patent Citations

  • Nano graphene platelet-based composite anode compositions for lithium ion batteries

    CN101849302A

  • Preparation method of stannic oxide or metallic tin and grapheme lamella composite material

    CN102255072A

  • Method for preparing tin dioxide / graphene-compounded anode material of lithium ion battery

    CN103078095A

  • Graphene-based composite negative electrode material, preparation method thereof and lithium ion battery

    CN103811718A

  • Method for preparing graphene-based hollow tin dioxide lithium ion battery negative electrode material

    CN104600275A